Palliative care in elderly patients challenges and symptom management strategies - Dias, Gabrielle Victoria Azevedo; Gonçalves, Mariana de Almeida Alves; Batista, Amanda Alves Feitosa (JRG Journal of Academic Studies, 2024)
Aging is a natural process, and regular and personalized medical care and monitoring are crucial for the well-being of elderly patients. The general objective of this study was to conduct a narrative review of the literature on palliative care for elderly patients, focusing on the main strategies for managing symptoms and the challenges faced by health teams in caring for this population. The methodology is a descriptive study, with a qualitative approach, of the narrative literature review type, based on the following steps: (1) identification of the theme; (2) choice of the guiding question; (3) search or sampling in the literature; (4) establishment of criteria for inclusion and exclusion of studies; (5) categorization and evaluation of the articles included in the review; (6) interpretation of the results and synthesis of the knowledge of the main results evidenced in the analysis of the included articles. The selected articles were based on publications from the last 5 years (2019-2024) in the following databases: PUBMED, Scientific Electronic Library Online (SCIELO) and Virtual Health Library (BVS), Latin American and Caribbean Literature in Health Sciences (LILACS) and Nursing Database (BDENF). The results found gathered 9 articles that addressed different aspects of the relationship between palliative care in elderly patients and the challenges and strategies for managing symptoms in nursing care. In the analysis of the data, there was a convergence among the authors regarding the complexity of palliative care in elderly patients, especially in symptom management and the need for a multidisciplinary approach. Finally, this care aims to improve quality of life through the relief of physical, psychological and emotional symptoms, respecting the particularities of each individual.